Supercapacitors: Transition‐Metal‐Free Biomolecule‐Based Flexible Asymmetric Supercapacitors (Small 34/2016). Issue 34 (September 2016) - Yang, Yun; Wang, Hua; Hao, Rui; Guo, Lin
Abstract : On page 4683, H. Wang L. Guo, and co‐workers present a novel transition‐metal‐free asymmetric supercapacitor (ACS) based on a biomolecule named lawsone (2‐hydroxy‐1, 4‐naphthoquinone), which is a natural component derived from henna. The ASC shows comparable or even higher energy densities compared to those of reported transition‐metal‐based ASCs, and provides a new strategy for the generation of versatile green ASCs by harnessing the natural pool of abundant redox‐active biomolecules.